ANALISIS STRATEGI PENGEMBANGAN PRODUK BUMDES SIAK KECIL BENGKALIS - Mashuri Mashuri; Kurniatul Fil Khoirin (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
The aim of this research is to determine strengths and weaknesses, opportunities and threats, as well as determine product development strategies in order to win market competition. This research was conducted at one of the BUMDES (Village-Owned Enterprises) Kencana Mandiri which is located in Tanjung Belit village, Siak District, Bengkalis Regency. The data analysis method uses a qualitative descriptive approach, data collection techniques are carried out using interviews, questionnaires and observation. SWOT analysis through the Internal Factor Analysis Strategy Matrix (IFAS) and the External Factor Analysis Strategy Matrix (EFAS). Based on the results of the analysis, BUMDES Kencana Mandiri has strengths and opportunities that are higher than its weaknesses and threats. In the quadrant analysis using the SWOT Diagram, BUMDes Kencana Mandiri is in quadrant 1 with a progressive strategy position. In a prime and stable position, it is possible for BUMDES Kencana Mandiri to continue running, developing, expanding and increasing growth to achieve maximum progress.